Potentiality of Growth Traits for Selection to Improve Productivity in Nilotic Cattle - Pitia, Milla; Muso, Jackson; Ahmed, Muna (Indonesian Journal of Agricultural Research, 2022)
Selection for traits of economic importance is crucial for improving productivity and reproductivity in livestock, including cattle. We investigated the prospects of using growth traits; viz: live-body weight (BW), absolute growth rate (AGR), relative growth rate (RGR), absolute maturing rate (AMR), and Kleiber ratio (KR) as bases for selection in Nilotic cattle, by examining the phenotypic correlations among these traits, using 125 male and 136 female calves reared under traditional husbandry system. In the experimental procedure, the heart girth (HG) and body length (BL) of each calf was measured at birth, and at the age of 2, 4, 6, 8, 10, 12, 14, and 16 months; then the BW at each age was derived, and used for estimating AGR, RGR, AMR, KR, and dry matter intake for maintenance (DMIm). AGR, RGR, AMR, or KR was calculated from 0~8 months (AGRÎ±, RGRÎ±, AMRÎ±, KRÎ±), 8~12 months (AGRÎ², RGRÎ², AMRÎ², KRÎ²), and 12~16 months (AGRÎ³, RGRÎ³, AMRÎ³, KRÎ³). Phenotypic correlations were determined using the Pearson's correlationÂ method. The results revealed that, BW, AGR, RGR, AMR, KR, and DMIm were inter-correlated. In particular, calf weaning weight (CWW at 8 months), and post-weaning AGRÎ², RGRÎ², AMRÎ², and KRÎ² (all at 8~12 months` interval) were positively correlated among themselves and with post-weaning BW, but negatively correlated with birth weight and DMIm, and thus, considered the most appropriate selection indices in Nilotic cattle, since these would decrease calf birth weight, thereby reducing dystocia incidences, and increase post-weaning growth, with less DMIm. These results provide the first evidence for possible selection using growth traits to improve productive efficiency in Nilotic cattle.